COST CONTROL STRATEGY AND ACCOUNTING EARNINGS OF QUOTED DEPOSIT MONEY BANKS IN NIGERIA - Syder, Inuadume Daniel; Akandu, Chituru Justice (Scholars Digest Publishing, 2025)
Despite the dynamic shocks from the global financial market, Nigerian banking management had to deal with domestic economic challenges like high inflation, a twist in monetary policy, and an industry environment that resulted in high operating costs and a risk profile that required innovative cost control mechanism. Predicated on these, cost control strategy and accounting earnings of quoted deposit money banks in Nigeria was examined. Banking industry cost objects as: Fee and commission expenses, Interest expenses and other operating expenses served as study dimensions while earnings after interest and tax measured accounting earnings. Correlational research design was adopted to obtain secondary data from the banks in the study purview by content analysis for 2013 to 2024 accounting periods. The data analysis involved: Descriptive statistics to ascertain the normal distribution of data series. Unit root test was done by Augmented Dickey Fuller and Phillips Perron Statistic tests to justify stationarity. These analytical tests were also carried out; Johansen Co-integration test to ascertain long-run relationship, Parsimonious Error Correction Model (PECM) to identify the speed at adjustment from short-run deviations. The estimations were done using E-views software. The results indicate that fee and commission expenses negatively but insignificantly related with earnings after interest and tax of quoted deposit money banks in Nigeria. Interest expenses positively and significantly impacts on earnings after interest and tax of quoted deposit money banks in Nigeria. Similarly, other operating expenses related positively and significantly on earnings after interest and tax of quoted deposit money banks in Nigeria. The study concludes that cost control strategy impacts significantly on accounting earnings of quoted deposit money banks in Nigeria. This is leveraging on investment in transforming digital technologies and innovative culture as was portrayed in the ideals of scientific management theory. It recommends that banking firms quoted in Nigeria should integrate and sustain the cost control strategy because it impacts significantly on accounting earnings leveraging on innovative smart technologies.